The Crisis in the Churches : Spiritual Malaise, Fiscal Woe. - Wuthnow, Robert (Oxford University Press, 1997)
This text examines the crises in America's churches. Pointing to both the failure of the clergy to confront their financial problems head-on, and their neglect of the real spiritual needs of their predominantly middle-class congregations, it offers suggestions for more effective ministry.